2011
DOI: 10.1124/mol.111.075135
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants of Pentamidine-Induced hERG Trafficking Inhibition

Abstract: Pentamidine is an antiprotozoal compound that clinically causes acquired long QT syndrome (acLQTS), which is associated with prolonged QT intervals, tachycardias, and sudden cardiac arrest. Pentamidine delays terminal repolarization in human heart by acutely blocking cardiac inward rectifier currents. At the same time, pentamidine reduces surface expression of the cardiac potassium channel I Kr /human ether à -gogo-related gene (hERG). This is unusual in that acLQTS is caused most often by direct block of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 55 publications
3
32
0
Order By: Relevance
“…1A and B), which illustrates that trafficking from the ER to the Golgi was impaired. In fact, increasing evidence shows that drugs affect hERG channels by interfering with their trafficking [5,12]. Numerous studies have shown that misfolding of hERG channels is most often the cause of defects in trafficking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1A and B), which illustrates that trafficking from the ER to the Golgi was impaired. In fact, increasing evidence shows that drugs affect hERG channels by interfering with their trafficking [5,12]. Numerous studies have shown that misfolding of hERG channels is most often the cause of defects in trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…For example, dofetilide and cisapride are proarrhythmic due to their acute blockade of hERG channels [2,3]. Arsenic trioxide, pentamidine and desipramine cause LQTS by altering hERG expression [4,5,6]. Importantly, most of these drugs alter hERG expression by interfering with its trafficking.…”
Section: Introductionmentioning
confidence: 99%
“…Although a drug’s EC 50 value for chaperoning is strongly correlated with its ligand binding affinity (Kd) and/or its ability to activate/inhibit its protein target [53,9496] chaperoning EC 50s are generally, but not always [97], 100 fold higher (i.e., less potent) than those required for functional activation/inhibition [80,81,95]. The lower potency of chaperoning presumably derives from lower affinity interactions with immature intermediates, relative to high-affinity interactions with native, mature conformations [71].…”
Section: Pharmacology Of Pcsmentioning
confidence: 99%
“…ER analysis is now routinely used to predict the QT effect in the targeted patient population, including clinical scenarios with doses and formulations not directly evaluated in the TQT study and QT effects in specific populations and under certain conditions (e.g., drug interactions) with increased exposure of the drug [13][14][15][16][17][18][19]. Extensive experience with QT-prolonging drugs demonstrate that the effect on the QT interval is directly related to plasma levels of the drug or main metabolites, with few exceptions (e.g., QT prolongation inhibition of hERG protein trafficking, which is delayed in relation to peak plasma levels [20][21][22]). In our view, it therefore makes sense to focus on QT effects in relation to plasma concentration of the drug, rather than by timepoint without consideration of the pharmacology of the drug, and a wider role for ER analysis in the assessment of drug-induced ECG effects seems justified.…”
Section: Introductionmentioning
confidence: 99%